Multi-scale model based design of membrane reactor/separator processes for intensified hydrogen production through the water gas shift reaction. (4th March 2020) - Karagöz, Seçgin; Tsotsis, Theodore T.; Manousiouthakis, Vasilios I.
Abstract: This work aims to first quantify the impact of various diffusion models (Maxwell-Stefan, Wilke, Dusty-Gas) on the predictions of a multi-scale membrane reactor/separator mathematical model, and to then demonstrate this model's use for the design and process intensification of membrane reactor/separator systems for hydrogen production. This multi-scale model captures velocity, temperature and species' concentration profiles along the catalyst pellet's radial direction, and along the reactor's axial direction, by solving the momentum, energy, and species transport equations, accounting for convection, conduction, reaction, and diffusion mechanisms. In the first part of work, the effect of pellet-scale design parameters (mean pore diameter, volumetric porosity, tortuosity factor, etc.) and various species' flux models on the model predictions is studied. In the second part, the study focuses on the comparison, in terms of their process intensification characteristics, of various hydrogen production processes. These include a conventional high-temperature shift reactor (HTSR)/low-temperature shift reactor (LTSR) sequence, a novel HTSR/membrane separator (MS)/LTSR/MS sequence, and a process that involves low-temperature shift membrane reactors-LTSMR in a series. Highlights: Dusty Gas Model comparison with other diffusion flux models, in membrane reactors. Multi-scale model simulation based process design. Membrane-Separator/Membrane-Reactor based WGSR intensifying designs.